2020
DOI: 10.3390/jcm9103150
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes Following Total Knee Replacement in Patients <65 Years of Age—A Systematic Review and Meta-Analysis

Abstract: An increasing number of total knee replacements (TKRs) are being performed in response to the growing burden of osteoarthritis. Patients <65 years of age represent the fastest growing group of TKR recipients and are expected to account for an increasing number of primary and revision procedures. Concerns have been raised about the outcomes that can be expected by this age demographic who are more active, physically demanding, and have longer life expectancies compared to older TKR recipients. This systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…All four studies (with serious risk of bias) examining satisfaction exhibited overall patient-reported satisfaction with TKR procedure [ 27 , 28 , 35 , 37 ]. These satisfaction results are consistent with the broader literature and studies analysing TKRs for younger patients [ 8 , 44 , 45 ]. Despite these findings, the measure of satisfaction is under the influence of a range of factors and thus remains a complex area.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…All four studies (with serious risk of bias) examining satisfaction exhibited overall patient-reported satisfaction with TKR procedure [ 27 , 28 , 35 , 37 ]. These satisfaction results are consistent with the broader literature and studies analysing TKRs for younger patients [ 8 , 44 , 45 ]. Despite these findings, the measure of satisfaction is under the influence of a range of factors and thus remains a complex area.…”
Section: Discussionsupporting
confidence: 91%
“…A prior systematic review and meta-analysis examined the patient-reported outcomes following TKR in patients aged less than 65 years [ 8 ]. This report found significant and meaningful improvements in pain, knee function, quality of life, and overall satisfaction with the procedure in individuals within this age demographic [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial increase in the number of TKR surgeries has also been reported in other countries 3 . TKR surgery typically results in functional knee range of motion and improved performance in daily life 4 . However, a significant number of patients experiences suboptimal outcomes, including falls and functional limitations after surgery 5,6 …”
Section: Introductionmentioning
confidence: 98%
“…The number of TKAs in patients under the age of 65 years notably increased in recent years [13, 23]. They represent the fastest growing population of TKA recipients and are expected to account for more than 50% of knee replacement procedures by the year 2030 [24].…”
Section: Introductionmentioning
confidence: 99%